Overview of the Resilience of the Poor in North Aceh During the Covid-19 Pandemic - Nurul Hastuti Nurdin; Safuwan Amin (Universitas Muhammadiyah Banjarmasin, 2022)
This study aims to examine the picture of resilience which includes the factors and processes of building resilience in the poor in North Aceh Regency in the face of the COVID-19 pandemic. The research method used is a phenomenological qualitative research type involving five subjects taken by purposive sampling method. The data collection process was carried out using the interview method as the main data collection method and observation as the supporting data collection method. Based on the research that has been done, it is found that the factors that shape the achievement of resilience of the subjects include gratitude, self-efficacy, never give up, optimistic and critical thinking, significant others, empathy, and coping transformation. While the process of forming resilience in the poor in facing poverty goes through stages, namely a) feeling bored and feeling sad, b) survival (surviving), c) Adjustment (Recovery) and d) Thriving (able to get through difficulties and take positive things from the difficulties faced by the poor). occur). So it can be concluded that the poor people of North Aceh have good resilience or resilience in dealing with poverty during the COVID-19 pandemic. This can be seen from the way people don't lament too much about the difficulties they face, stay calm and stay productive during the pandemic.